Symbolic significance and its effectiveness in industrial product design (Al-Academy, 2022)
The current research dealt with the symbolic significance and its effectiveness in the design of the industrial product, the aesthetic communicative discourse that embodies the imagination and human conscience. Whether according to what has been termed custom or what has been approved by traditions long ago, symbolism may be the main actor in linking the identifying components of the product. In addition, symbolism provides the user with the key to accessing a direct awareness of the product’s shape and function, as an identification of the product by stimulating the symbolic form of the consumer’s imagination and inviting him to To meditate in order to realize the implicit meaning behind these forms and thus achieve the symbolism of the work. (Symbolic significance in industrial design, types of significance, symbolic indications of structural design elements, color processors in design systems and their symbolic indications, light and transparency in design systems and their symbolic indications, smart materials and the significance of design thought)